Resolution of Skin Fibrosis by Neutralization of the Antifibrinolytic Function of Plasminogen Activator Inhibitor 1. Issue 2 (February 2016) - Lemaire, Raphaël; Burwell, Timothy; Sun, Hong; Delaney, Tracy; Bakken, Julie; Cheng, Lily; Rebelatto, Marlon C.; Czapiga, Meggan; de‐Mendez, Isabelle; Coyle, Anthony J.; Herbst, Ronald; Lafyatis, Robert; et al.
Abstract : Objective: Systemic sclerosis (SSc) is a fibrotic disease characterized by an obliterative vasculopathy with thrombosis and impairment of the coagulation–fibrinolysis balance. Plasminogen activator inhibitor 1 (PAI‐1) is the major inhibitor of profibrinolytic plasminogen activators (PAs). This study was undertaken to evaluate the contribution of PAI‐1 to SSc pathology in the skin. Methods: PAI‐1 was evaluated in skin from patients with diffuse SSc (dSSc) and those with limited SSc (lSSc) by immunohistochemistry. The contribution of PAI‐1 to SSc pathology was tested in vivo in murine graft‐versus‐host disease (GVHD) and bleomycin models of progressive skin fibrosis and in vitro in dermal human microvascular endothelial cells (HMVECs) using a monoclonal antibody that selectively prevents the binding of PAI‐1 to PA. Results: Skin from patients with dSSc and those with lSSc showed increased PAI‐1 levels in the epidermis and microvessel endothelium. PAI‐1 neutralization in the GVHD model led to a dramatic, dose‐dependent improvement in clinical skin score, concomitant with vasculopathy resolution, including a reduction in fibrinolysis regulators and vascular injury markers, as well as reduced inflammation. Resolution of vasculopathy and inflammation was associated with resolution of skin fibrosis, as assessed by reduction in collagen content and expression of key profibrotic mediators, including transforming growth factor β1 and tissue inhibitor of metalloproteinases 1. Similar to the GVHD model, PAI‐1 neutralization reduced dermal inflammation and fibrosis in the bleomycin model. PAI‐1 neutralization stimulated plasmin‐mediated metalloproteinase 1 activation in dermal HMVECs. Conclusion: Our findings indicate that neutralization of the antifibrinolytic function of PAI‐1 resolves skin fibrosis by limiting the extent of initial vascular injury and connective tissue inflammation. These data suggest that PAI‐1 represents an important checkpoint in disease pathology in human SSc.